2023
DOI: 10.1007/s12020-023-03420-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism, lipids, and lipidomics

Abstract: Purpose Hypothyroidism is a relatively common endocrine disorder and is well documented to be associated with lipid abnormalities. Methods A narrative review was conducted of studies describing the alterations in the lipid profile accompanying both subclinical and overt hypothyroidism. Results Lipid abnormalities are seen with TSH values in the upper end of the accepted reference range, as well as with subclinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
2
0
1
Order By: Relevance
“…The data are consistent with the results of pathway analysis (see Section 2.3) as they show details regarding specific variations of different classes of metabolites, identifying either common metabolic signatures of PTC and BT or specific alterations for each pathology group, compared to controls. These findings are consistent with other previous experimental data obtained by LC-MS or NMR analysis of serum PTC and/or BT (hypo-and hyperthyroidism) samples that also confirmed the presence of specific alterations of these metabolic pathways [24,25,[34][35][36][37][38][39][40][41].…”
Section: Differential Statistics For Each Class Of Molecules Involved...supporting
confidence: 93%
See 1 more Smart Citation
“…The data are consistent with the results of pathway analysis (see Section 2.3) as they show details regarding specific variations of different classes of metabolites, identifying either common metabolic signatures of PTC and BT or specific alterations for each pathology group, compared to controls. These findings are consistent with other previous experimental data obtained by LC-MS or NMR analysis of serum PTC and/or BT (hypo-and hyperthyroidism) samples that also confirmed the presence of specific alterations of these metabolic pathways [24,25,[34][35][36][37][38][39][40][41].…”
Section: Differential Statistics For Each Class Of Molecules Involved...supporting
confidence: 93%
“…In addition, increased levels of bile acids were correlated with the upregulated FFA metabolism, which was observed in the BT group. These data are confirmed by the findings of different study groups [24,25,[33][34][35][36][37][38][39][40][41][42][43][44][45][46], their results being related to the same categories of metabolites.…”
Section: Discussionsupporting
confidence: 74%
“…A large amount of data was available on the effect of high TSH levels and SCH in women with PCOS, whereas fewer studies analyzed the influence of other thyroid diseases/dysfunctions, such as AIT and GD, in women with PCOS. SCH was associated with a decrease in glucose disposal, but an increase in serum SHBG, total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, and total triglyceride (TG) levels, weight, and insulin resistance in the general population, particularly in women ( 138 141 ). In fact, thyroid hormones regulate lipid and carbohydrate metabolism via direct actions on gene expression or nuclear receptors ( 142 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human studies have shown a positive correlation between elevated serum TSH levels and increased atherosclerotic lipid profiles, even within the normal reference range. Additionally, thyroid hormone replacement therapy, which reduces TSH levels, has been associated with lower blood lipid levels and a delayed progression of AS ( 28 ). Another study showed that serum TSH levels were positively correlated with cholesterol, even within the normal reference range, which also validated the influence of TSH on lipid metabolism ( 16 ).…”
Section: Discussionmentioning
confidence: 99%